2017
DOI: 10.1002/asia.201700586
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Doped Graphitic Porous Carbon Nanosheets Derived from In Situ Formed g‐C3N4 Templates for the Oxygen Reduction Reaction

Abstract: Heteroatom-doped carbon materials have been considered as potential substitutes for Pt-based electrocatalysts for the oxygen reduction reaction (ORR) in alkaline fuel cells. Here we report the synthesis of oxygen-containing nitrogen-doped carbon (ONC) nanosheets through the carbonization of a mixture that contained glucose and dicyandiamide (DCDA). In situ formed graphitic carbon nitride (g-C N ) derived from DCDA provided a nitrogen-rich template, thereby facilitating the formation of ONC nanosheets. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 80 publications
(46 reference statements)
2
29
0
Order By: Relevance
“…[43,44] The intensity ratio (I D /I G )o f Fe-containing CMs slightly decreased from 1.18 to 1.13 with increasingc arbonization temperature (Table S2), attesting to the higher graphitic degree corresponding to the resultso f XRD. [45,46] Co or Cu-containing CMs exhibit the same results. However,t he graphitization degree of CMs is still low,w hich may be due to ac ollapse of porous graphitic frameworks and defects in graphite structure induced by an introduction of heteroatoms.…”
Section: Resultssupporting
confidence: 56%
“…[43,44] The intensity ratio (I D /I G )o f Fe-containing CMs slightly decreased from 1.18 to 1.13 with increasingc arbonization temperature (Table S2), attesting to the higher graphitic degree corresponding to the resultso f XRD. [45,46] Co or Cu-containing CMs exhibit the same results. However,t he graphitization degree of CMs is still low,w hich may be due to ac ollapse of porous graphitic frameworks and defects in graphite structure induced by an introduction of heteroatoms.…”
Section: Resultssupporting
confidence: 56%
“…The weak CO peak may be attributed to the presence of C(O)OH, originating from the precursors or O‐containing species on the surface of fibrous carbon. The high‐resolution N 1s spectroscopy displayed three prominent peaks, corresponding to pyridinic‐N (398.0 eV), pyrrolic‐N (400.1 eV), and graphitic‐N (401.0 eV) . Incorporating N‐species (particularly pyridinic‐N and graphitic‐N) into the carbon matrix has a positive impact on enhancing the overall electrical conductivity and wettability, thus accelerating the transfer of electron and charge .…”
Section: Resultsmentioning
confidence: 99%
“…The key to success of HCSs in various applications is based on the availability of precisely controlled diameter and shell thickness, surface chemistry, and dispersibility in media. Numerous investigations have been devoted to the synthesis of porous carbon spheres via various strategies, including hard or soft‐templating method, emulsion self‐assembly process, and stöber‐based routes . Among the studies reported, many have focused on the preparation of hollow structural units with tunable sizes.…”
Section: Introductionmentioning
confidence: 99%